Symbiosis aquaculture revitalization & coastal defense system of Manila Bay - Ong, Colleen Krystle N. (College of Architecture, University of the Philippines Diliman, 2022)
The Philippines is known to have one of the largest coastlines in the world, with a plethora of life found within their shores. With this, and the archipelagic geography of the country, many Filipinos have their livelihoods depending on the country’s coastlines like those in Manila Bay. Recent human activity, however, has caused a degradation on the shores through different malpractices and rapid urbanization, resulting in threats like food insecurity, and an aggravation of coastal geological hazards. The proposed project aims to create a critical coastal supplement— a structure that could help in boosting the location it can be found in. Symbiosis would be proposing a new typology of inhabitable infrastructure, combining coastal defense with aquaculture systems. It would cater to the needs of the coastal communities by providing physical safety and food security to the area. Using a combination of qualitative and quantitative studies, as well as interviews with experts, the proposed project reflects various technologies and systems to ensure its sustainability and efficiency, while also maintaining a familiarity for the users of the space. Symbiosis creates an architectural solution that includes all the necessary facilities, areas, and elements of seawalls and aquaculture systems, combining them seamlessly into a single structure. Besides this, the project also caters to those around it, with a community area placed for locals with explorational design elements to provide a more experiential visit. In conclusion, the physical elements of the seawall and technical systems of aquaculture can go hand in hand, especially with their linkage of water to form a sustainable aquaculture and coastal defense system for Manila Bay. With urbanization and human negligence continuously occurring and aggravating the country’s environmental situation, structures like Symbiosis could be the answer to eliminating the fragility of coastal areas.